1996
DOI: 10.1210/mend.10.5.8732681
|View full text |Cite
|
Sign up to set email alerts
|

Cross-coupling between insulin and estrogen receptor in human neuroblastoma cells.

Abstract: Insulin is a well known mitotic agent for neuroblastoma cells. Human SK-N-BE neuroblastoma cells stably transfected with the estrogen receptor, however, undergo growth arrest and differentiation when treated with insulin. These effects were shown to be due to an insulin-dependent activation of the unliganded estrogen receptor. Here, we demonstrate that this activation involves the AF-2 COOH-terminal domain of the estrogen receptor and that the communication between estrogen and insulin receptor systems occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…The increase in basal transcription observed when ERα was added to the transfection mixture, was attributed to the presence of growth factors present in the stripped serum and responsible for ligand-independent activation of ER. Such an effect has been already reported by our and other groups [32]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The increase in basal transcription observed when ERα was added to the transfection mixture, was attributed to the presence of growth factors present in the stripped serum and responsible for ligand-independent activation of ER. Such an effect has been already reported by our and other groups [32]. …”
Section: Resultssupporting
confidence: 88%
“…Attempts were made to carry out the cotransfection experiments also in neuroblastoma SK-N-BE, a cell system proved to be useful to investigate other estrogen-responsive promoters [32, 33](fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…In line with this cross-talk between ERa and EGF, mice which have ERa inactivated (aERKO mice) lack the uterine E2-like response to EGF even though the EGF signaling pathway is not disrupted (Curtis et al, 1996). Other growth factors which activate ERa signaling include insulin (Newton et al, 1994;Patrone et al, 1996Patrone et al, , 1998, insulin-like growth factor-1 (IGF-1) (Aronica and Katzenellenbogen, 1993;Ma et al, 1994;Newton et al, 1994;Ignar-Trowbridge et al, 1996), and TGF-b (Ignar-Trowbridge et al., 1996). In addition, heregulin, interleukin-2, and dopamine (Power et al, 1991;Smith et al, 1993;Pietras et al, 1995) can also modulate ER activity.…”
Section: Effect Of Cell Signaling-induced Phosphorylation On Estrogenmentioning
confidence: 99%
“…The role of IGF-1 receptor as regulator of ER␣ transcriptional activity has also been characterized in neuronal cells. Maggi and co-workers have determined that insulin/IGF-1 signaling can activate the unliganded ER␣ in neuronal cells via the ras/MAPK pathway [63,64] and that this activation involved the N-terminal activation function 1 (AF-1) domain of the receptor [65]. More recent studies have shown that although IGF-1 promotes ligand-independent ER transcriptional activity, it has a different effect in the presence of estradiol.…”
Section: Interactions Between Estrogen Receptor ␣ and Igf-1 Receptor mentioning
confidence: 99%